SARS-CoV-2 vertical transmission supports innate fetal protection: A narrative review - Barnea, Eytan R.; Di Simone, Nicoletta; Hayrabedyan, Soren; Todorova, Krassimira; Inversetti, Annalisa; Vento, Giovanni; Costa, Simonetta (Frontiers in Virology, 2022)
Prenatal infections that have been exhaustively studied help frame the current Severe Acute Respiratory Syndrome related coronavirus-2 (SARS-CoV-2) pandemic, with the caveat that asymptomatic SARS-CoV-2 infected patients are not tested, while those symptomatic are delivered and/or treated with drug(s) available on-site. Thus, management and therapy are still heterogeneous. SARS-CoV-2 induced respiratory infection remains mostly local, unless severe, which lessens transplacental vertical transmission (VT). Vaccination prior to or during pregnancy significantly changes the prognosis for both the mother and newborn. The virus spread to the fetus can be binding to ACE2 and TMPRSS2 protein receptors. A recent study demonstrated ACE2 and TMPRSS2 fetal expression in the intestine from the second trimester. Most placental infections are subclinical unless severe villitis and apoptosis are observed. The placenta is rarely tested, and it is highly probable that most are positive for the virus, requiring sophisticated diagnostics to document. Other VT modalities, such as vaginal, rectal or through amniotic fluid contamination, are very rare. Therefore, vaginal delivery is preferable when clinically feasible. It has not yet been determined whether the placenta is a shield or if it transmits infection, while, on the other hand, recent data support fetal resilience, which is plausible due to the major difference between the placental and fetal rates of infection: only 3%–5% of documentable VT compared with up to 100% expected placental exposure to viremia. Newborn Polymerase Chain Reaction (PCR) from nasal swab is more practical as an option for VT diagnosis compared to ocular or anal swab, with low yield. The maternal infection leads to antiviral IgG production of 100% in severe cases, which is transferred to the fetus and breast milk. Postpartum-documenting VT is difficult since horizontal viral transmission may be common and minimized by mother/staff/family-preventive measures. Breastfeeding is safe and encouraged because, beyond nutrition, it promotes protective antibody transfer and maternal bonding. Lessons learned from other Betacorona viruses (SARS-CoV and Middle East Respiratory Syndrome related coronavirus [MERS-CoV]) virulence are relevant since mutations can increase or decrease vulnerability. Overall, data support fetal/newborn resilience against SARS-CoV-2 VT. However, viremia monitoring by sensitive tests and assessment for delayed sequelae shown in adults is necessary.